Digitalisation and rural tourism development in Europe - Nuria Alonso Gallo; Lucía Vicent; David Trillo (Tourism & Management Studies)
This work presents an analysis of the digitalisation of the tourism sector and evaluates the potential of this process for rural areas of the European Union (EU). To do this, we explore aspects of both the supply and demand of rural tourism, proposing a regression model that incorporates indicators that relate the advance of digitalisation with changes in the weight and characteristics of the sector in the regions with low population density included in the NUTS level 2. The research results indicate a positive relationship between the digitalisation of the sector and the supply of rural accommodation, as well as a positive impact on the demand for these facilities. In addition, the study has made it possible to address the potential competition between traditional accommodations and digital platforms, revealing that the greater use of digital platforms for reservations does not negatively affect hotel occupancy rates. The findings underline the importance of digitalisation in the development of rural tourism and suggest possible lines of political action for promoting digital platforms in rural areas.